KEPRIBADIAN, KOMUNIKASI, KELOMPOK TEMAN SEBAYA, IKLIM SEKOLAH DAN PERILAKU BULLYING - Usman, Irvan (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstractNowadays, bullying is common among students. Previous researches explored the causes and the effect of bullying among students. This research was aimed to explore the role of personality, communication, peer and school climate to bullying among senior high school students in Gorontalo.The subjects were 103 students. Data was collected through personality scale, communication scale, peer influence scale, school climate scale and bullying scale. This research was quantitative research with regression analysis. A research result shows that personality, communication, peer and school climate influence bullying among senior high school students in Gorontalo.Keywords: bullying, communication, peer, personality, school climate